The Effect of Adding Fly Ash Waste on the Compressive Strength and Water Absorption of Brick Bricks - Rangga, Luckiantoro; Kristianto, Anang (Jurnal Teknik Sipil, 2025)
The method of reduce waste from coal combustion from Steam Power Plant activities to add fly ash into the brick mixture. The small particles can reduce voids in the brick, thereby increasing compressive strength and reduce water absorption This research aims to utilize fly ash Pesona Khatulistiwa Nusantara LLC as an environmentally friendly brick mixture which is expected to increase compressive strength and reduce water absorption. This analysis was conducted based on SNI 03-0349-1989, data validation through experimental tests by making variations of brick test specimens. Each variable has a different percentage of fly ash composition, the composition in the laboratory uses wet fly ash is 0%, 10%, 20%, 30%, 35%, 40% and the composition on site using wet fly ash is 0%, 10%, 20%, 25%, 30%, there is an additional variable of 20% dry fly ash. This difference in composition takes the best 4 results from laboratory testing. The result of testing bricks with 30% fly ash addition on site had the highest compressive strength of 21.04 Mpa with an average water absorption of 9.45%, these bricks have been categorized as category I with water absorption.